2021
DOI: 10.1590/acb360207
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide restores late cardioprotective effects of remote preconditioning in diabetic rats via activation of hydrogen sulfide and nuclear factor erythroid 2-related factor 2 signaling pathway

Abstract: Purpose The present study explored the influence of liraglutide on remote preconditioning-mediated cardioprotection in diabetes mellitus along with the role of nuclear factor erythroid 2-related factor 2 (Nrf2), hypoxia inducible factor (HIF-1α) and hydrogen sulfide (H 2 S). Methods Streptozotocin was given to rats to induce diabetes mellitus and rats were kept for eight weeks. Four cycles of ischemia and reperfusion were given to hind limb to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Accumulating evidence has shown that targeting GLP-1 signaling is an effective approach to improving cardiovascular outcomes in preclinical models of diabetes [ 61 ]. Our findings of liraglutide’s cardioprotective role through modulation of oxidative stress align with previous findings [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that targeting GLP-1 signaling is an effective approach to improving cardiovascular outcomes in preclinical models of diabetes [ 61 ]. Our findings of liraglutide’s cardioprotective role through modulation of oxidative stress align with previous findings [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, as a transcription factor, Nrf2 triggers the production of many phase II detoxifying and antioxidant enzymes through the activation of heme-oxygenase 1 and NADPH quinone oxidoreductase gene expression, which protect cells under conditions of oxidative stress [ 206 , 207 , 208 ] and provides cellular protection against different toxins [ 206 , 209 , 210 , 211 ]. In fact, several studies have shown that the activation of Nrf2 and the subsequent upregulation of antioxidant enzyme gene expression is an important mechanism of cardioprotection due to ischemic/hypoxic preconditioning, and that low concentrations of ROS may be an essential signal for the protective process [ 212 , 213 , 214 , 215 ]. Furthermore, Nrf2 has also been reported to modulate intracellular Ca 2+ levels [ 216 ], and thus cardioprotection against I/R injury due to the activation of Nrf2 has recently been explored for clinical applicability [ 199 ].…”
Section: Modification Of I/r-induced Defects In Signal Transductionmentioning
confidence: 99%